2018
DOI: 10.1111/peps.12276
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and burdens of organizational reputation for employee well‐being: A conservation of resources approach

Abstract: We consider the possibility that a positive organizational reputation brings both benefits and burdens to employees working for those organizations. Drawing from the “Red Queen” notion in competitive strategy and from conservation of resources theory, we argue that although organizational reputation can cause employees to identify more strongly with the organization, it may also pressure employees to commit more of their time to the job. In turn, increased organizational identification and time commitment have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 131 publications
(334 reference statements)
0
16
0
1
Order By: Relevance
“…Thus, there are more job demands than supply. According to the CoR theory, when resources are lost or perceived to be threatened, people experience stress and are motivated to gain back their resources (Baer et al, 2018 ). Under the economic lockdown and recession, more students may have difficulties in finding jobs and/or internships, which could negatively affect students' self-esteem (personal resource) and their individual economic well-being (object resource) for instance.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Thus, there are more job demands than supply. According to the CoR theory, when resources are lost or perceived to be threatened, people experience stress and are motivated to gain back their resources (Baer et al, 2018 ). Under the economic lockdown and recession, more students may have difficulties in finding jobs and/or internships, which could negatively affect students' self-esteem (personal resource) and their individual economic well-being (object resource) for instance.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…When individual needs of self-enhancement and self-distinctiveness are fulfilled (Dutton et al, 1994), PES may have a stronger influence on employee engagement. Indeed, past research has shown that media representation influences reputation (Meadows & Meadows, 2016), which can lead employees to identify more strongly with their employer and improve morale (Baer et al, 2018).…”
Section: Media Representationmentioning
confidence: 99%
“…According to COR theory, when environmental conditions deplete or threaten finite and valued resources of individuals (i.e. actual or expected resources losses), they experience strain and suffer from resource depletion (Baer et al ., 2018; Lanaj et al ., 2018; Lapointe, Vandenberghe and Panaccio, 2011; Pingel, Fay and Urbach, 2019). In line with this theory, perceived role overload reflects a state of depleted resources (Baer et al ., 2015; Campbell et al ., 2013).…”
Section: Theory and Hypothesesmentioning
confidence: 99%